In Blind Pursuit of Racial Equality? - Apfelbaum, Evan P.; Pauker, Kristin; Sommers, Samuel R.; Ambady, Nalini (Psychological Science, 2010)
Despite receiving little empirical assessment, the color-blind approach to managing diversity has become a leading institutional strategy for promoting racial equality, across domains and scales of practice. We gauged the utility of color blindness as a means to eliminating future racial inequity—its central objective—by assessing its impact on a sample of elementary-school students. Results demonstrated that students exposed to a color-blind mind-set, as opposed to a value-diversity mind-set, were actually less likely both to detect overt instances of racial discrimination and to describe such events in a manner that would prompt intervention by certified teachers. Institutional messages of color blindness may therefore artificially depress formal reporting of racial injustice. Color-blind messages may thus appear to function effectively on the surface even as they allow explicit forms of bias to persist.